Grundlagen der medikamentösen Schmerztherapie - Schüning, Julia; Schwarzer, Andreas (DMW - Deutsche Medizinische Wochenschrift, 2018)
Many chronic diseases or their consequences are associated with pain. Furthermore, the pain itself can become the disease. Pharmaceuticals are an important component in the treatment of pain. This article presents different analgesic drugs, their mode of action, indications, dosage and adverse drug reactions.
Keywords: Schmerztherapie; Opioide; Nichtsteroidale Antirheumatika; Schwangerschaft; Geriatrie